2007
DOI: 10.1128/jvi.02468-06
|View full text |Cite
|
Sign up to set email alerts
|

The X Protein of Borna Disease Virus Serves Essential Functions in the Viral Multiplication Cycle

Abstract: The X gene of Borna disease virus (BDV) encodes a nonstructural 10-kDa protein that can interact with viral polymerase cofactor P, thus regulating polymerase activity. It remained unknown whether X is essential for virus multiplication. All our attempts to generate mutant BDV with a nonfunctional X gene proved unsuccessful. However, a mutant virus with an inactive X gene was able to replicate in Vero cells if an artificial gene cassette encoding X was inserted at a site near the 5 end of the viral genome. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…BDV non-cytolytic replication depends on the expression of an 87 amino acids viral protein called X 10 . This non-structural protein was initially described as an important regulator of viral RNA synthesis and of polymerase complex assembly in the nucleus of infected cells [11][12][13] . Later, it was shown that X represents the first mitochondrion-localized protein of an RNA virus that inhibits rather than promotes induction of apoptosis, thereby favouring non-cytolytic viral persistence 10 and escape to mitochondrial antiviral signalling protein-mediated host cell defence 14 .…”
mentioning
confidence: 99%
“…BDV non-cytolytic replication depends on the expression of an 87 amino acids viral protein called X 10 . This non-structural protein was initially described as an important regulator of viral RNA synthesis and of polymerase complex assembly in the nucleus of infected cells [11][12][13] . Later, it was shown that X represents the first mitochondrion-localized protein of an RNA virus that inhibits rather than promotes induction of apoptosis, thereby favouring non-cytolytic viral persistence 10 and escape to mitochondrial antiviral signalling protein-mediated host cell defence 14 .…”
mentioning
confidence: 99%
“…G is the viral envelope glycoprotein and is involved in BDV entry, involving virion attachment to an unknown receptor and fusion of the viral envelope and cell membrane to release the vRNP into the cell cytoplasm in association with host factors [16][17][18][19][20][21]. X is a multifunctional, non-structural protein that is essential for the viral replication cycle [22], and is known to be a regulator of viral polymerase activity and an inhibitor of apoptosis in the central nervous system [23 -25].…”
mentioning
confidence: 99%
“…The L protein is tightly regulated by N-P stoichiometric ratio (Schneider, 2005;Schneider et al, 2005;Walker et al, 2000;Walker and Lipkin, 2002). The X protein is 10kDA protein, interacts with P protein and, acts as a negative regulator of BDV polymerase and hinders viral replication (Poenisch et al, 2004;Poenisch et al, 2007;Schwardt et al, 2005).…”
mentioning
confidence: 99%